2018
DOI: 10.1002/1878-0261.12367
|View full text |Cite
|
Sign up to set email alerts
|

ABCA1 overexpression worsens colorectal cancer prognosis by facilitating tumour growth and caveolin‐1‐dependent invasiveness, and these effects can be ameliorated using the BET inhibitor apabetalone

Abstract: At the time of diagnosis, 20% of patients with colorectal cancer present metastasis. Among individuals with primary lesions, 50% of them will develop distant tumours with time. Therefore, early diagnosis and prediction of aggressiveness is crucial for therapy design and disease prognosis. Tumoral cells must undergo significant changes in energy metabolism to meet increased structural and energetic demands for cell proliferation, and metabolic alterations are considered to be a hallmark of cancer. Here, we pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
93
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 46 publications
6
93
0
1
Order By: Relevance
“…Furthermore, the fact that AKT1 [74], that regulates COAD metastasis, altered in both TCGA-COAD as well as COAD-metastasis and showed association with FSS, ROS, and HCMDB-COAD is one of the most prominent results. Another noteworthy result of the OncoPrint analysis was the emergence of the transporter proteins, ABCA1 and SLC7A2 ( Figure 6a), which mediated cell invasion and tumor progression in COAD cells respectively [75,76]. Our result that SLC7A2 showed significant gene alteration in COAD but not in metastasis is supported by the literature [76].…”
Section: Oncoprint Analysis and Survival Analyses Of The Selected Mrnsupporting
confidence: 76%
“…Furthermore, the fact that AKT1 [74], that regulates COAD metastasis, altered in both TCGA-COAD as well as COAD-metastasis and showed association with FSS, ROS, and HCMDB-COAD is one of the most prominent results. Another noteworthy result of the OncoPrint analysis was the emergence of the transporter proteins, ABCA1 and SLC7A2 ( Figure 6a), which mediated cell invasion and tumor progression in COAD cells respectively [75,76]. Our result that SLC7A2 showed significant gene alteration in COAD but not in metastasis is supported by the literature [76].…”
Section: Oncoprint Analysis and Survival Analyses Of The Selected Mrnsupporting
confidence: 76%
“…Apart from poor nutritional status frequently seen in CRC (20), which could be one of the reasons for decreased cho-lesterol synthesis in the liver, it has been recently proposed that reprogramming of lipid metabolism could be responsible for the observed decrease in serum lipid status markers in various types of cancer (20,21). Namely, it has been demonstrated that cancer cells extensively accumulate and use cholesterol (22,23), while such increased needs are satisfied by either upregulated endogenous synthesis (24), or enhanced uptake of circulating cholesterol (25,26). Such rearrangement of cholesterol synthesis and cellular accumulation could have important consequences regarding vitamin D status.…”
Section: Discussionmentioning
confidence: 99%
“…Although without biological activity, 25-hydroxyvitamin D (25(OH)D3) is generally accepted as a reliable marker of vitamin D status (8). However, recent evidences have emphasized 24,25-dihydroxyvitamin D (24,25 (OH) 2 D3), a catabolic product with negligible biological activity, as a promising marker for prediction of vitamin D deficiency and several associated pathological conditions (9). Accordingly, the ratio between 25(OH)D3 and 24,25(OH) 2 D3, or vitamin D metabolite ratio (VDMR) might provide more accurate insight into vitamin D status and more precise prediction of possible effects of disturbed vitamin D levels (10).…”
Section: Metabolism Of Vitamin D Is Complex and Includes Several Intementioning
confidence: 99%
“…The ATP-binding cassette transporter ABCA1 is a transmembrane protein responsible for the reverse cholesterol transport from the inner cell to circulatory system. ABCA1 is significantly overexpressed in patients of all stages of CRC, and its overexpression gives proliferative advantages together with caveolin-1-dependent increased migratory and invasive capacities (151). Individuals with upregulation of ABCA1 expression have an improved risk of CRC recurrence and OS independently of tumor stage (8).…”
Section: Cholesterol-related Alterations As Biomarkers Of Cancer Progmentioning
confidence: 99%